Fireweed (Heartleaf Nettle) Control in Pastures - Brent Sellers; Jason Ferrell; Pratap Devkota (EDIS)
Fireweed (Urtica chamaedryoides) (Figure 1) is native to Florida, but has only recently become problematic. This winter annual species is commonly observed in north and central Florida pastures, particularly in bareground areas (near feeding pens and under fences), as well as along tree lines where forage grasses are less dense. This 2-page fact sheet is a minor revision written by B. Sellers, J. Ferrell, and P. Devkota, and published by the Agronomy Department, December 2019.